Knowledge and attitude regarding breastfeeding - Jannesari, Sh; Dolatian, M; Alavi majd, H (Advances in Nursing & Midwifery, 2008)
Background Infant feeding decisions depend on knowledge and attitudes toward breast feeding, which may be formed as early as adolescence. Purpose The purpose of this descriptive study was to assess knowledge as well as attitude of female non-medical students regarding breast feeding in selected universities of Tehran in 2006. Methods 800 students selected by multi-stage cluster randomized sampling took part in the study. A questionnaire completed by the subjects was used to collect data. Content and test-retest methods were used for its validity and reliability respectively. Results 51.6% of the students had moderate knowledge and 41.6% had good knowledge regarding breast feeding. Knowledge of engineering students was more than the others. In addition, 75.4% of the subjects had positive attitude toward the feeding. There was a significant difference between attitude scores in three knowledge levels (good, moderate, poor) (P<0.01) Conclusion Findings showed that students need more knowledge in some aspects to have more positive attitude for performing a successful breast-feeding program. Keywords Knowledge, Attitude, Breast feeding.